The Effectiveness of the Sikat Jaran Candi Operation in Reducing the Crime of Theft in the Legal Territory of the Semarang Polrestabes - Muhammad Sukma Indra Faturahman (Police Studies Review, 2021)
Crime from time to time shows a very significant increase, both in small cities and in big cities in Indonesia, such as the capital city of Jakarta, Bandung, Yogyakarta, Semarang and other big cities. Increased crime in Indonesia can be caused by a booming population, especially in cities with large numbers of jobs, the lifestyle of people in urban areas which tends to be high which requires them to have their own vehicle to do their daily work. The high number of vehicles in the city of Semarang also increases the crime rate of vehicle theft which results in disruption of order and security for the community, members of the Police who are tasked with guarding this have taken action, one of which is through sikat jaran operations to reduce the crime of vehicle theft. Therefore, the researcher conducted this study to determine whether the operation carried out by the Semarang Police was effective or not or not at all effective and looked for factors that influenced the success of this operation. To analyze these problems, the researcher used the theory of effectiveness and law enforcement theory, for the concept the researcher used the concept of the criminal unit, the concept of the operation of the sikat jaran and the concept of patrol. The approach used is qualitative and the method used is field research. Data sources were obtained by researchers from primary and secondary data sources. The results of the research obtained were that there were still a few obstacles faced by the Elang Team members such as lack of facilities and infrastructure, lack of personnel and lack of community participation and professional criminal offenders, however the results obtained by the Elang Team always found full success. Suggestions from researchers from this study are the addition of personnel and facilities to support this operation considering the perpetrators are getting smarter and more professional, and educating the public so they can play a role in reporting to prevent this crime.